Botanical origin authentication of dietary supplements by DNA‐based approaches - Grazina, Liliana; Amaral, Joana S.; Mafra, Isabel (Comprehensive reviews in food science and food safety, 2020)
Herbal products, such as dietary supplements, have become a subject of increasing global importance for their health benefits and economic considerations. However, they have also been targets of adulteration practices, being the accurate identification of botanicals in herbal products of utmost importance to protect the health and expectations of consumers. Particularly, in the case of dietary supplements, which can have different types of formulations, the identification of plant material used in their production is often a research challenge. DNA‐based techniques have played a crucial role on the development of a wide range of tools for the authentication of herbal products. Therefore, this review intends to describe their main progresses, critically discussing their advantages and drawbacks when applied to authenticate herbal products, focusing on dietary supplements. DNA barcoding is particularly emphasized because it has provided the highest number of applications, followed by the advances on high‐resolution melting analysis combined with DNA barcodes. A special emphasis is also given to the promising approaches relying on DNA metabarcoding and isothermal amplification.